2022
DOI: 10.3389/fimmu.2022.850616
|View full text |Cite
|
Sign up to set email alerts
|

Contact-Dependent Granzyme B-Mediated Cytotoxicity of Th17-Polarized Cells Toward Human Oligodendrocytes

Abstract: Multiple sclerosis (MS) is characterized by the loss of myelin and of myelin-producing oligodendrocytes (OLs) in the central nervous system (CNS). Pro-inflammatory CD4+ Th17 cells are considered pathogenic in MS and are harmful to OLs. We investigated the mechanisms driving human CD4+ T cell-mediated OL cell death. Using fluorescent and brightfield in vitro live imaging, we found that compared to Th2-polarized cells, Th17-polarized cells show greater interactions with primary human OLs and human oligodendrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“…Furthermore, we observed upregulation of FASL on Th17 cells from long-term, but not short-term, NAT patients. Another publication illustrated the relevance of contact-dependent granzyme B-mediated cytotoxicity of Th17 cells upon coculture with human oligodendrocytes, which at least indirectly supports our finding of altered apoptotic pathways induced upon coculture with Th17 cells derived from long-term NAT-treated MS patients ( 44 ). However, at least in the context of NAT treatment, we did observe an altered expression of granzyme B or TRAIL neither on MCAM+CCR6+Th17 cells nor in the supernatants upon coculture with either EC or oligodendrocytes ( SI Appendix , Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, we observed upregulation of FASL on Th17 cells from long-term, but not short-term, NAT patients. Another publication illustrated the relevance of contact-dependent granzyme B-mediated cytotoxicity of Th17 cells upon coculture with human oligodendrocytes, which at least indirectly supports our finding of altered apoptotic pathways induced upon coculture with Th17 cells derived from long-term NAT-treated MS patients ( 44 ). However, at least in the context of NAT treatment, we did observe an altered expression of granzyme B or TRAIL neither on MCAM+CCR6+Th17 cells nor in the supernatants upon coculture with either EC or oligodendrocytes ( SI Appendix , Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Pro‐inflammatory T helper 17 cells (Th17) are pathogenic in MS and EAE. Recent studies reported that Th17 cells directly contacted oligodendrocytes in MS and EAE 85 and that Th17 cell‐derived granzyme B was toxic to human oligodendrocytes in vitro 86 . These data suggest that Serpina3n/SERPINA3 expression in oligodendrocytes may protect them from inflammation‐induced injury/death, presumably through dampening lymphocyte‐derived granzyme B—a similar hypothetic mechanism to the one discussed in neuronal cell death/survival (Section 8).…”
Section: Hypothetical Role Of Serpina3n/serpina3 In Demyelinating Dis...mentioning
confidence: 77%
“…Recent studies reported that Th17 cells directly contacted oligodendrocytes in MS and EAE 85 and that Th17 cell-derived granzyme B was toxic to human oligodendrocytes in vitro. 86…”
Section: Hypothetical Role Of Serpina3n/ Serpina3 In Demyelinating Di...mentioning
confidence: 99%
“…S5, C and D, and data file S2). Another CD4 + CTL cluster was observed along with the T H A cluster, likely cytotoxic T H 17 ( 49 51 ), because these cells expressed high levels of RORC and CCR6 . ADGRG1 , encoding GPR56 and identified in T H A SEGs using RNA-seq (Fig.…”
Section: Resultsmentioning
confidence: 99%